Comportamento informacional na tomada de decisão: proposta de Modelo Integrativo - Frederico Cesar Mafra Pereira (2011)
This thesis aimed to propose a theoretical-conceptual model to demonstrate the information flows in the processes of search and use of the information used by managers of micro and small enterprises (MSEs) in strategic decisions. The theoretical work was based on identifying information needs, seeking processes and use of information models, as well as organizational strategic decision making models. The main methodological research approach used in the thesis was to study of the type 'formulator or exploratory', which allowed the construction and propose several models, which were consolidated into Integrative Model: information behavior for strategic decisions. As a test of this model, we conducted interviews with managers of MSE located in Belo Horizonte, Minas Gerais. The results show the applicability of the Integrative Model and constituent models, confirming the methodological procedures adopted in the thesis, both for the development of the Integrative Model and the search´s test.